2008
DOI: 10.1523/jneurosci.5306-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Odor Responses from Antennal Neurons of Gqα, Phospholipase Cβ, andrdgAMutants inDrosophilaSupport a Role for a Phospholipid Intermediate in Insect Olfactory Transduction

Abstract: Mechanisms by which G-protein-coupled odorant receptors transduce information in insects still need elucidation. We show that mutations in the Drosophila gene for G q ␣ (dgq) significantly reduce both the amplitude of the field potentials recorded from the whole antenna in responses to odorants as well as the frequency of evoked responses of individual sensory neurons. This requirement for G q ␣ is for adult function and not during antennal development. Conversely, brief expression of a dominant-active form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 50 publications
8
117
0
Order By: Relevance
“…In contrast, another study indicates an additional metabotropic response requiring the recruitment of G-proteinmediated second-messenger pathways that is delayed and slower relative to the initial ionotropic response (Wicher et al 2008). Although the question remains open, the incorporation of G-protein dependent pathways that presumably require the synthesis of second-messenger intermediates is also consistent with numerous studies linking ORs to GPCR signalling pathways (Kain et al 2008, Kalidas and Smith 2002, Woodard et al 1992.…”
Section: Mosquito Olfactory Transduction: a Road Map Under Constructionsupporting
confidence: 59%
See 1 more Smart Citation
“…In contrast, another study indicates an additional metabotropic response requiring the recruitment of G-proteinmediated second-messenger pathways that is delayed and slower relative to the initial ionotropic response (Wicher et al 2008). Although the question remains open, the incorporation of G-protein dependent pathways that presumably require the synthesis of second-messenger intermediates is also consistent with numerous studies linking ORs to GPCR signalling pathways (Kain et al 2008, Kalidas and Smith 2002, Woodard et al 1992.…”
Section: Mosquito Olfactory Transduction: a Road Map Under Constructionsupporting
confidence: 59%
“…The initial and very fast response is cAMP-independent, while a second and much more sensitive response is G s -mediated and cAMP-dependent. More or less simultaneously Kain et al (2008) showed very strong evidence for a G q and a phospholipase C involvement. The transduction system is not clearly understood, and contains a number of different transduction pathways.…”
Section: Transduction Mechanismsmentioning
confidence: 95%
“…In insects, both metabotropic [16][17][18] and inotropic [19][20] mode of signaling have been proposed to mediate olfactory transduction at ORNs. Until recently, insect ORs were considered to be a member of GPCRs [21][22]; however, new evidence suggests that insect ORs exhibit a different membrane topology and differ in OR protein sequence from vertebrate ORs [23][24].…”
Section: Short-communicationmentioning
confidence: 99%
“…Surprisingly, though, both the insect gustatory and olfactory receptors act as ligand-gated cation channels when expressed in heterologous cell culture systems (Sato et al, 2008;Wicher et al, 2008). Perhaps even more surpris-ingly, several studies have reported conflicting results using different expression systems and experimental approaches and concluded that at least some members of the superfamily couple to G proteins (Kain et al, 2008;Wicher et al, 2008).…”
Section: Olfactory Co 2 Detection Mechanismsmentioning
confidence: 99%